2007
DOI: 10.4315/0362-028x-70.4.835
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the BAX Gel and Fluorometric Systems for the Detection of Foodborne Salmonella

Abstract: The present study compared the sensitivity of the BAX automated fluorometric and the recently discontinued BAX gel electrophoresis systems with a standard culture method to detect Salmonella in 333 high-moisture and 171 low-moisture foods. A total of 95 naturally contaminated foods, including 63 high-moisture and 32 low-moisture foods, were detected by the standard culture method. No contaminated samples were identified exclusively by the BAX systems. By means of the analytical protocol stipulated by the manuf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Although many commercial PCR kits include easy‐to‐use sample treatments protocols that (apparently) work, independent studies show a remarkably low diagnostic sensitivity when testing naturally contaminated samples (D’Aoust et al., 2007).…”
Section: Current Developmentsmentioning
confidence: 99%
“…Although many commercial PCR kits include easy‐to‐use sample treatments protocols that (apparently) work, independent studies show a remarkably low diagnostic sensitivity when testing naturally contaminated samples (D’Aoust et al., 2007).…”
Section: Current Developmentsmentioning
confidence: 99%
“…Quantitative real time PCR (qRTPCR), provides great target specificity, particularly among those that utilize target-specific probes. However independent studies have demonstrated that the accuracy of PCR based methods, in general, might be challenged when testing naturally contaminated samples as their sensitivity can be compromised by intrinsic or extrinsic factors (D'Aoust et al, 2007;Hoorfar, 2011). These challenges involve the inability of differentiating viable from dead cells, without significant additional sample processing, or those cells that can be in a viable but not culturable physiological condition (VBNC) (Moyne, Harris, & Marco, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Reports on the comparison of performance between the BAX system and other analytical methods, for example, the immunoassay-based and the standard reference culture methods, for Salmonella detection are also available. The BAX system was found to have very low false-positive and false-negative rate and generated results comparable with those of the standard culture methods, ISO 6579, HPA F13, and MFHPB-20 (Cheung et al, 2007;D'Aoust & Purvis, 1998;D'Aoust et al, 2007;Tomazelli et al, 2008). Furthermore, for raw samples with higher background flora inoculated with Salmonella Typhi, positive results could be obtained with the BAX system, whereas false negatives were generated by the immunoassay-based Tecra Unique™ Salmonella test and the standard culture method (Cheung et al, 2007).…”
Section: Detection Of Salmonella In Food Samples By Conventional and mentioning
confidence: 71%